Spatial Tooth Profile Design of Triple-circular-arc Harmonic Gears and Finite Element Simulation of Torsional Stiffness - Xing Jingzhong; Chen Liang; Chen Xiaoxia; Yao Yunpeng (Jixie chuandong)
In order to improve the transmission capability by exploring the relationship between torsional stiffness on output shaft and load meshing characteristics, a simulation model of finite element analysis (FEA) is built to evaluate the performance of tooth profile under transmission loading. A triple-circular-arc tooth profile of flexspline is constructed, and the radial modification of the tooth profile is adjusted to minimize the outer envelope overlap of meshing motion of the tooth profiles. Then, a triple-circular-arc planar tooth profile of circular splines is designed with the envelop method according to the outer envelope. A triple-circular-arc tooth profile of flexspline with tradial modification is constructed in several cross sections, and the spatial tooth profiles of flexsplines are generated by axial lofting in finite element environment. A finite element simulation model including circular spline with planar tooth profile, cup-shaped flexspline with spatial tooth profile and outer ring of wave generators is established. Transmission torques of different amplitudes in two rotational directions are applied on the flange plate at the bottom of the flexspline engaged with a fixed circular spline, and the meshing force distribution and torsional stiffness hysteresis curves are simulated. The number of meshing teeth in different meshing states can be estimated with the relationship between torsional stiffness and meshing characteristics of tooth profiles. The simulation results show that the number of meshing teeth is positively correlated with the torsional stiffness. Using the measureable hysteresis curve of torsional stiffness, the immeasurable meshing characteristics such as the number of meshing teeth can be estimated.